Who are the targets of familial electoral coercion? Evidence from Turkey. Issue 8 (17th November 2019) - Toros, Emre; Birch, Sarah
ABSTRACT: The unfettered expression of electoral choice is an important democratic right; however, in many contexts voters are pressured by others to cast their votes in certain ways. Electoral coercion is a topic that has received increased attention from researchers in recent years as part of the wave of research on electoral violence, yet there is little consensus in the literature as to who the targets of coercion are most likely to be. This article uses a list experiment embedded in a survey fielded following the Turkish general election of 2018 to identify the targets of coercive electoral practices within families and among close friends. The analysis reveals familial electoral coercion to be strongly conditioned by partisanship and disadvantaged demographic characteristics, but finds no evidence that women are more likely than men to be coerced.